Fungicide resistant isolates of the blue mold pathogen, Penicillium expansum, are stable, exhibit differences in fitness penalties, and cause decay on apple fruit - Riley S. Harding; Verneta L. Gaskins; Dianiris Luciano-Rosario; Wayne M. Jurick; Kerik D. Cox (Postharvest Biology and Technology, 2026)

A qualitative exploration of women's experiences of food insecurity around pregnancy aligned with the socio-ecological model - J. Marshall; L. Davies; Lambeth HDRC; F. Lavelle; N. O'Leary; A.C. Flynn; S. Harding; Z. Bell (Appetite, 2026)

Juvenile salmon prey sampled at sea using a pelagic rope trawl and a frame trawl - Jeffrey A. Harding; Ilysa S. Iglesias; Brian K. Wells; Whitney R. Friedman; David D. Huff (Fisheries Research, 2025)

Night shift work and indicators of cardiovascular risk: A systematic review and meta-analysis - Johanna Samulin Erdem; Mrinal K. Das; Evi De Ryck; Øivind Skare; Jenny-Anne S. Lie; Merete Bugge; Barbara Harding; Ingrid L. Jorgensen; Ingrid Sivesind Mehlum; Manolis Kogevinas; Karl-Christian Nordby; Shan Zienolddiny-Narui (Environmental Research, 2025)

The impacts of alien species on river bioassessment - Maria João Feio; Janine P. da Silva; Robert M. Hughes; Francisca C. Aguiar; Carlos B.M. Alves; Sebastian Birk; Marcos Callisto; Marden S. Linares; Diego R. Macedo; Paulo S. Pompeu; Wayne Robinson; Christian Schürings; et al. (Journal of Environmental Management, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

The Fourth Global Coral Bleaching Event: Where do we go from here? - James Davis Reimer; Raquel S. Peixoto; Sarah W. Davies; Nikki Traylor-Knowles; Morgan L. Short; Rafael A. Cabral-Tena; John A. Burt; Igor Pessoa; Anastazia T. Banaszak; R. Scott Winters; Tom Moore; Verena Schoepf; et al. (Coral Reefs, 2024)

Factors influencing occupational exposure to pyrethroids and glyphosate: An analysis of urinary biomarkers in Malaysia, Uganda and the United Kingdom - William Mueller; Kate Jones; Samuel Fuhrimann; Zulkhairul Naim Bin Sidek Ahmad; Craig Sams; Anne-Helen Harding; Andrew Povey; Aggrey Atuhaire; Ioannis Basinas; Martie van Tongeren; Hans Kromhout; Karen S. Galea (Environmental Research, 2024)

High-altitude characterization of the Hunga pressure wave with cosmic rays by the HAWC observatory - Ruben Alfaro; César Alvarez; Juan Carlos Arteaga-Velázquez; Arun Babu Kollamparambil Paul; Daniel Avila Rojas; Hugo Alberto Ayala Solares; Rishi Babu; Ernesto Belmont-Moreno; Chad Brisbois; Karen S. Caballero-Mora; Tomás Capistrán; Alberto Carramiñana; et al. (Advances in Space Research, 2024)

Changing processes flooding a salt marsh in a microtidal estuary with a drying climate - Gavan S. McGrath; Carolyn Harding; Pascal Matte (Estuarine, Coastal and Shelf Science, 2023)

LP-18: Challenges and Opportunities in Use of the Minipig for Nonclinical Pharmaceutical Development: Results of the Second IQ DruSafe Minipig Survey - J. Harding; K. Datta; D. Olaharski; D. Clarke; T. Flandre; K. French; M. Leach; S. Mohr; D. Strein; B. Gauthier (Toxicology Letters, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Redox conditions and ecological resilience during Oceanic Anoxic Event 2 in the Western Interior Seaway - L.J. Robinson; K.S. George; C.P. Fox; J.E.A. Marshall; I.C. Harding; P.R. Bown; J.R. Lively; S. Marroquín; R.M. Leckie; S. Dameron; D.R. Gröcke; N.M. Papadomanolaki; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Wind regime changes in the Euro-Atlantic region driven by Late-Holocene Grand Solar Minima - P. Harding; C. Martin-Puertas; J. Sjolte; A. A. Walsh; R. Tjallingii; C. Langdon; S. P. E. Blockley; A. Brauer; P. Langdon; A. M. Milner; R. Muscheler; M. Perez (Climate Dynamics, 2023)

Fish and macroinvertebrate assemblages reveal extensive degradation of the world's rivers - Maria João Feio; Robert M. Hughes; Sónia R. Q. Serra; Susan J. Nichols; Ben J. Kefford; Mark Lintermans; Wayne Robinson; Oghenekaro N. Odume; Marcos Callisto; Diego R. Macedo; Jon S. Harding; Adam G. Yates; et al. (Global Change Biology, 2023)
Rivers suffer from multiple stressors acting simultaneously on their biota, but the consequences are poorly quantified at the global scale. We evaluated the biological condition of rivers globally, including the largest proportion of countries from the Global South published to date. We gathered macroinvertebrate‐ and fish‐based assessments from 72,275 and 37,676 sites, respectively, from 64 study regions across six continents and 45 nations. Because assessments were based on differing methods, different systems were consolidated into a 3‐class system: Good, Impaired, or Severely Impaired, following common guidelines. The proportion of sites in each class by study area was calculated and each region was assigned a Köppen‐Geiger climate type, Human Footprint score (addressing landscape alterations), Human Development Index (HDI) score (addressing social welfare), % rivers with good ambient water quality, % protected freshwater key biodiversity areas; and % of forest area net change rate. We found that 50% of macroinvertebrate sites and 42% of fish sites were in Good condition, whereas 21% and 29% were Severely Impaired, respectively. The poorest biological conditions occurred in Arid and Equatorial climates and the best conditions occurred in Snow climates. Severely Impaired conditions were associated (Pearson correlation coefficient) with higher HDI scores, poorer physico‐chemical water quality, and lower proportions of protected freshwater areas. Good biological conditions were associated with good water quality and increased forested areas. It is essential to implement statutory bioassessment programs in Asian, African, and South American countries, and continue them in Oceania, Europe, and North America. There is a need to invest in assessments based on fish, as there is less information globally and fish were strong indicators of degradation. Our study highlights a need to increase the extent and number of protected river catchments, preserve and restore natural forested areas in the catchments, treat wastewater discharges, and improve river connectivity.

Discovery of three cycloviruses in fecal samples from silver-haired bats (Lasionycteris noctivagans) in Arizona (USA) - Ciara Harding; Brendan B. Larsen; Sophie Gryseels; Hans W. Otto; Crystal Suazo; Simona Kraberger; Nathan S. Upham; Michael Worobey; Koenraad Van Doorslaer; Arvind Varsani (Archives of Virology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Lipoid liver disease in Hippocampus erectus Perry with Vibrio fortis ‐induced dermatitis and enteritis - Drayke Evans; Zachary Millar; Danielle Harding; Phuc H. Pham; Véronique LePage; John S. Lumsden (Journal of Fish Diseases, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Middle Pleistocene environments, landscapes and tephrostratigraphy of the Armenian Highlands: evidence from Bird Farm 1, Hrazdan Valley - Jenni E. Sherriff; Keith N. Wilkinson; Poppy Harding; Hayley Hawkins; Rhys G. O. Timms; Daniel S. Adler; Emily J. Beverly; Simon P. E. Blockley; Boris Gasparyan; Christina J. Manning; Darren Mark; Samvel Nahapetyan; et al. (Journal of Quaternary Science, 2022)
The significance of the southern Caucasus in understanding Pleistocene hominin expansions is well established. However, the palaeoenvironments in which Palaeolithic occupation of the region took place are presently poorly defined. The Hrazdan river valley, Armenian Highlands, contains a rich Palaeolithic record alongside Middle Pleistocene volcanic, fluvial and lacustrine strata, and thus offer exciting potential for palaeoenvironmental reconstruction. We present the first results of sedimentological, geochemical, tephrostratigraphical and biological (diatoms) study of the sequence of Bird Farm 1, located in the central part of the valley. These data show six phases of landscape development during the interval 440–200 ka. The sequence represents the first quantitative Pleistocene diatom record from the Armenian Highlands and the southern Caucasus, and indicates the persistence of a deep, stratified lacustrine system, with evidence for changing lake productivity that is tentatively linked to climate. Furthermore, major element chemical characterization of visible and crypto‐tephra horizons in the sequence enables the first stages of the development of a regional tephrostratigraphy. Together, the evidence from Bird Farm 1 demonstrates the importance of lacustrine archives in the region for palaeoenvironmental reconstruction and highlights the potential for linkages between archives on both a local and regional scale.

The genetic architecture of target‐site resistance to pyrethroid insecticides in the African malaria vectors Anopheles gambiae and Anopheles coluzzii - Chris S. Clarkson; Alistair Miles; Nicholas J. Harding; Andrias O. O’Reilly; David Weetman; Dominic Kwiatkowski; Martin J. Donnelly (Molecular Ecology, 2021)
Resistance to pyrethroid insecticides is a major concern for malaria vector control. Pyrethroids target the voltage‐gated sodium channel (VGSC), an essential component of the mosquito nervous system. Substitutions in the amino acid sequence can induce a resistance phenotype. We use whole‐genome sequence data from phase 2 of the Anopheles gambiae 1000 Genomes Project (Ag1000G) to provide a comprehensive account of genetic variation in the Vgsc gene across 13 African countries. In addition to known resistance alleles, we describe 20 other non‐synonymous nucleotide substitutions at appreciable population frequency and map these variants onto a protein model to investigate the likelihood of pyrethroid resistance phenotypes. Thirteen of these novel alleles were found to occur almost exclusively on haplotypes carrying the known L995F kdr (knock‐down resistance) allele and may enhance or compensate for the L995F resistance genotype. A novel mutation I1527T, adjacent to a predicted pyrethroid‐binding site, was found in tight linkage with V402L substitutions, similar to allele combinations associated with resistance in other insect species. We also analysed genetic backgrounds carrying resistance alleles, to determine which alleles have experienced recent positive selection, and describe ten distinct haplotype groups carrying known kdr alleles. Five of these groups are observed in more than one country, in one case separated by over 3000 km, providing new information about the potential for the geographical spread of resistance. Our results demonstrate that the molecular basis of target‐site pyrethroid resistance in malaria vectors is more complex than previously appreciated, and provide a foundation for the development of new genetic tools for insecticide resistance management.

ASL expression in ALDH1A1+ neurons in the substantia nigra metabolically contributes to neurodegenerative phenotype - Shaul Lerner; Raya Eilam; Lital Adler; Julien Baruteau; Topaz Kreiser; Michael Tsoory; Alexander Brandis; Tevie Mehlman; Mina Ryten; Juan A. Botia; Sonia Garcia Ruiz; Alejandro Cisterna Garcia; et al. (Human Genetics, 2021)
Argininosuccinate lyase (ASL) is essential for the NO-dependent regulation of tyrosine hydroxylase (TH) and thus for catecholamine production. Using a conditional mouse model with loss of ASL in catecholamine neurons, we demonstrate that ASL is expressed in dopaminergic neurons in the substantia nigra pars compacta, including the ALDH1A1 + subpopulation that is pivotal for the pathogenesis of Parkinson disease (PD). Neuronal loss of ASL results in catecholamine deficiency, in accumulation and formation of tyrosine aggregates, in elevation of α-synuclein, and phenotypically in motor and cognitive deficits. NO supplementation rescues the formation of aggregates as well as the motor deficiencies. Our data point to a potential metabolic link between accumulations of tyrosine and seeding of pathological aggregates in neurons as initiators for the pathological processes involved in neurodegeneration. Hence, interventions in tyrosine metabolism via regulation of NO levels may be therapeutic beneficial for the treatment of catecholamine-related neurodegenerative disorders.

Benthic Invertebrate Indices Show No Response to High Nitrate-Nitrogen in Lowland Agricultural Streams - Thomas P. Moore; Catherine M. Febria; Angus R. McIntosh; Helen J. Warburton; Jon S. Harding (Water, Air, & Soil Pollution, 2021)

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

A Pharmacokinetic Analysis of Hemodialysis for Metformin-Associated Lactic Acidosis - Stephen A. Harding; Rana Biary; Robert S. Hoffman; Mark K. Su; Mary Ann Howland (Journal of Medical Toxicology, 2021)

Development of a pro-arrhythmic ex vivo intact human and porcine model: cardiac electrophysiological changes associated with cellular uncoupling - Joseph Brook; Min-young Kim; Simos Koutsoftidis; David Pitcher; Danya Agha-Jaffar; Annam Sufi; Catherine Jenkins; Konstantinos Tzortzis; Suofeiya Ma; Richard J. Jabbour; Charles Houston; Balvinder S. Handa; et al. (Pflügers Archiv - European Journal of Physiology, 2020)
We describe a human and large animal Langendorff experimental apparatus for live electrophysiological studies and measure the electrophysiological changes due to gap junction uncoupling in human and porcine hearts. The resultant ex vivo intact human and porcine model can bridge the translational gap between smaller simple laboratory models and clinical research. In particular, electrophysiological models would benefit from the greater myocardial mass of a large heart due to its effects on far-field signal, electrode contact issues and motion artefacts, consequently more closely mimicking the clinical setting. Porcine ( n = 9) and human ( n = 4) donor hearts were perfused on a custom-designed Langendorff apparatus. Epicardial electrograms were collected at 16 sites across the left atrium and left ventricle. A total of 1 mM of carbenoxolone was administered at 5 ml/min to induce cellular uncoupling, and then recordings were repeated at the same sites. Changes in electrogram characteristics were analysed. We demonstrate the viability of a controlled ex vivo model of intact porcine and human hearts for electrophysiology with pharmacological modulation. Carbenoxolone reduces cellular coupling and changes contact electrogram features. The time from stimulus artefact to (-dV/dt) max increased between baseline and carbenoxolone (47.9 ± 4.1–67.2 ± 2.7 ms) indicating conduction slowing. The features with the largest percentage change between baseline and carbenoxolone were fractionation + 185.3%, endpoint amplitude − 106.9%, S-endpoint gradient + 54.9%, S point − 39.4%, RS ratio + 38.6% and (-dV/dt) max − 20.9%. The physiological relevance of this methodological tool is that it provides a model to further investigate pharmacologically induced pro-arrhythmic substrates.

Trialling tools using hand‐weeding, weed mat and artificial shading to control nuisance macrophyte growth at multiple scales in small agricultural waterways - Kathryn E. Collins; Catherine M. Febria; Hayley S. Devlin; Kristy L. Hogsden; Helen J. Warburton; Brandon C. Goeller; Angus R. McIntosh; Jon S. Harding (New Zealand Journal of Marine and Freshwater Research, 2020)
Introduced aquatic macrophytes can dominate small agricultural waterways in summer and autumn becoming a significant management problem. Excessive growth can clog waterways, causing drainage issues and reducing agricultural productivity while in‐stream velocities are reduced and sedimentation increased. Consequently, water managers remove them by mechanical clearance, chemical spray and cutting which can be costly and have negative impacts on in‐stream habitat and ecological health. We trialled three tools to reduce macrophytes: hand‐weeding, weed mat and artificial shading, at a reach‐scale (50 m) and larger‐scale (200–400 m). Hand‐weeding reduced cover in the short‐term, however macrophytes recovered to pre‐treatment levels within one season. Weed mat along the banks was effective at reducing emergent macrophytes, particularly Erythranthe guttata (monkey musk) and Nasturtium microphyllum (watercress). Weed mat lasted for several growing seasons and continued to be effective. Shading over the waterway using polythene markedly reduced submerged macrophytes indicating that heavy shading by riparian plantings could reduce submerged macrophytes in the longer‐term. These results indicate that in the short‐term, weed mat could be used to limit sprawling emergent macrophytes. In the longer‐term, weed mat used in conjunction with riparian planting could provide shading so that macrophyte cover in these small waterways could be reduced and controlled.

Changes in stream food‐web structure across a gradient of acid mine drainage increase local community stability - Justin P. F. Pomeranz; Jeff S. Wesner; Jon S. Harding (Ecology, 2020)
Understanding what makes food webs stable has long been a goal of ecologists. Topological structure and the distribution and magnitude of interaction strengths in food webs have been shown to confer important stabilizing properties. However, our understanding of how variable species interactions affect food‐web structure and stability is still in its infancy. Anthropogenic stress, such as acid mine drainage, is likely to place severe limitations on the food‐web structures availabe, due to changes in community composition and body mass distributions. Here, we used mechanistic models to infer food‐web structure and quantify stability in streams across a gradient of acid mine drainage. Multiple food webs were iterated for each community based on species pairwise interaction probabilities, in order to incorporate the variability of realistic food‐web structure. We found that food‐web structure was altered systematically with a 32‐fold decrease in the number of links and a twofold increase in connectance across the gradient. Stability generally increased sixfold with increasing acid mine drainage stress, regardless of how interaction strengths were estimated. However, the distribution of the stability measure, s , for some impacted communities separated into clusters of higher and lower magnitude depending on how interaction strengths were estimated. Management and restoration of impacted sites needs to consider their increased stability, as this may have important implications for the recolonization of desirable species. Furthermore, active species introductions may be required to overcome the internal ecological inertia of affected communities.

Ecological processes mediate the effects of the invasive bloom-forming diatom Didymosphenia geminata on stream algal and invertebrate assemblages - J. P. Bray; C. Kilroy; P. Gerbeaux; F. J. Burdon; J. S. Harding (Hydrobiologia, 2020)

Differences in reported sun protection practices, skin cancer knowledge, and perceived risk for skin cancer between rural and urban high school students - Elizabeth S. Nagelhout; Bridget G. Parsons; Benjamin Haaland; Kenneth P. Tercyak; Kelsey Zaugg; Angela Zhu; Garrett Harding; Jeffrey Yancey; Jakob D. Jensen; Douglas Grossman; David W. Wetter; Yelena P. Wu (Cancer Causes & Control, 2019)

Faecal indicator bacteria in New Zealand freshwater fish: a pilot study - Sarah Coxon; Jon S Harding; Brent Gilpin (New Zealand Journal of Marine and Freshwater Research, 2019)
Recent studies have suggested that poikilothermic animals, such as fish, may represent a previously overlooked source of the faecal indicator bacteria (FIB) used for the assessment of water quality. However, quantitative studies of FIB in poikilotherms are scarce. We investigated the presence of FIB in the faeces of five freshwater fish species. E. coli and enterococci were detected in 71 and 76% of faecal samples, respectively. Concentrations were highly variable, with maximum concentrations (2.1 × 10 4 E. coli and 1.3 × 10 6 enterococci per gram of faecal material) up to four orders of magnitude higher than present in the water column. FIB were not detected in faecal samples from marine fish. Our findings suggest that FIB ingested from the environment may be capable of replication within the fish gut, making fish a potential source and transport mechanism for FIB in New Zealand freshwaters. This may have implications for water quality monitoring.

Evaluating practical macrophyte control tools on small agricultural waterways in Canterbury, New Zealand - Kathryn E. Collins; Catherine M. Febria; Helen J. Warburton; Hayley S. Devlin; Kristy L. Hogsden; Brandon C. Goeller; Angus R. McIntosh; Jon S. Harding (New Zealand Journal of Marine and Freshwater Research, 2019)
Excessive macrophytes can cause significant problems in agricultural waterways requiring active management. Conventional control techniques can have a range of adverse effects. We investigated several control tools in two experiments: firstly, we tested eight treatments at a small‐scale (2 m × 2 m). We found intensive hand weeding, weed mat and herbicide spraying to be effective treatments, reducing macrophyte cover to

Assessing the availability of life cycle assessments in Austria - A. O. Ladenika; Michael Oluwatosin Bodunrin; Nicholas W. Burman; Joel Croft; Shaun Engelbrecht; Taahira Goga; O. S. MacGregor; Mpho Maepa; Kevin G. Harding (The International Journal of Life Cycle Assessment, 2019)

Invasive Nitrogen-Fixing Plant Amplifies Terrestrial–Aquatic Nutrient Flow and Alters Ecosystem Function - Simon D. Stewart; Megan B. Young; Jon S. Harding; Travis W. Horton (Ecosystems, 2019)

Review: the availability of life-cycle studies in Sweden - Joel Croft; Shaun Engelbrecht; A. O. Ladenika; O. S. MacGregor; Mpho Maepa; Michael Oluwatosin Bodunrin; Nicholas W. Burman; Taahira Goga; Kevin G. Harding (The International Journal of Life Cycle Assessment, 2019)

The availability of life-cycle assessment, water footprinting, and carbon footprinting studies in Brazil - Michael O. Bodunrin; Nicholas W. Burman; Joel Croft; Shaun Engelbrecht; Taahira Goga; A. O. Ladenika; O. S. MacGregor; Mpho Maepa; Kevin G. Harding (The International Journal of Life Cycle Assessment, 2018)

A discussion on the availability of life-cycle assessment studies in New Zealand - Shaun Engelbrecht; A. O. Ladenika; O. S. MacGregor; Mpho Maepa; Michael O. Bodunrin; Nicholas W. Burman; Joel Croft; Taahira Goga; Kevin G. Harding (The International Journal of Life Cycle Assessment, 2018)

Review: life-cycle assessment, water footprinting, and carbon footprinting in Portugal - Nicholas W. Burman; Joel Croft; Shaun Engelbrecht; A. O. Ladenika; O. S. MacGregor; Mpho Maepa; Michael Oluwatosin Bodunrin; Kevin G. Harding (The International Journal of Life Cycle Assessment, 2018)

Fishes in a changing world: learning from the past to promote sustainability of fish populations - T. A. C. Gordon; H. R. Harding; F. K. Clever; I. K. Davidson; W. Davison; D. W. Montgomery; R. C. Weatherhead; F. M. Windsor; J. D. Armstrong; A. Bardonnet; E. Bergman; J. R. Britton; et al. (Journal of Fish Biology, 2018)
Populations of fishes provide valuable services for billions of people, but face diverse and interacting threats that jeopardize their sustainability. Human population growth and intensifying resource use for food, water, energy and goods are compromising fish populations through a variety of mechanisms, including overfishing, habitat degradation and declines in water quality. The important challenges raised by these issues have been recognized and have led to considerable advances over past decades in managing and mitigating threats to fishes worldwide. In this review, we identify the major threats faced by fish populations alongside recent advances that are helping to address these issues. There are very significant efforts worldwide directed towards ensuring a sustainable future for the world's fishes and fisheries and those who rely on them. Although considerable challenges remain, by drawing attention to successful mitigation of threats to fish and fisheries we hope to provide the encouragement and direction that will allow these challenges to be overcome in the future.

Acute toxicity of arsenic to larvae of four New Zealand freshwater insect taxa - Olivier Champeau; Jo Anne E. Cavanagh; Thomas J. Sheehan; Louis A. Tremblay; Jon S. Harding (New Zealand Journal of Marine and Freshwater Research, 2017)
Arsenic, often found in gold deposits, can enter aquatic systems. The toxicity of arsenate (As(V)), the most common valence state of arsenic in freshwater, was assessed on the larvae of four freshwater insect taxa from naturally acidic (pH 5.9) and circumneutral (pH 7.4) New Zealand streams. Insects from the acidic stream were more sensitive to arsenate‐spiked water than those from the circumneutral stream. Early instars ( Deleatidium spp. (Leptophlebiidae) were the most sensitive compared to later instars (3–6 mm) (4‐d LC 50 1.5 and 3.5 mg/L, respectively) or to the stonefly Zelandobius spp. (Gripopterygidae) (4‐d LC 50 2.5 mg/L). The cased caddisflies Pycnocentria spp. (Conoesucidae) and Helicopsyche spp. (Helicopsychidae) from circumneutral stream were the most tolerant (4‐d LC 50 45.4 and 113 mg/L, respectively). The 14‐day arsenic LC 10 and LC 50 for Deleatidium spp. late instars exposed to mining‐impacted water were 0.12 and 0.36 mg/L, respectively.

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Review: life cycle assessments in Nigeria, Ghana, and Ivory Coast - Mpho Maepa; Michael Oluwatosin Bodunrin; Nicholas W. Burman; Joel Croft; Shaun Engelbrecht; A. O. Ladenika; O. S. MacGregor; Kevin G. Harding (The International Journal of Life Cycle Assessment, 2017)

Production of phosphatase and extracellular stalks as adaptations to phosphorus limitation in Didymosphenia geminata (Bacillariophyceae) - Jon Bray; Jon O’Brien; Jon S. Harding (Hydrobiologia, 2017)

Disentangling the stream community impacts of Didymosphenia geminata: How are higher trophic levels affected? - Phillip G. Jellyman; Jon S. Harding (Biological Invasions, 2016)

Development and evaluation of a porcine in vitro colon organ culture technique - Matheus O. Costa; John C. S. Harding; Janet E. Hill (In Vitro Cellular & Developmental Biology - Animal, 2016)

Comparing total body lipid content of young‐of‐the‐year Steller sea lions among regions of contrasting population trends - Lorrie D. Rea; Brian S. Fadely; Sean D. Farley; Julie P. Avery; Wendy S. Dunlap‐Harding; Vicki K. Stegall; Carrie A. B. Eischens; Tom S. Gelatt; Kenneth W. Pitcher (Marine Mammal Science, 2016)
Steller sea lion ( Eumetopias jubatus ) young‐of‐the‐year ( YOY ) are nutritionally dependent upon their dam through the majority of their first year. Several indices of body condition were measured in YOY 1.5–9 mo of age captured in Southeast Alaska ( n = 122), the Gulf of Alaska ( n = 182), and the Aleutian Islands ( n = 38) to test the hypothesis that nutritional stress impacted the ability of adult female Steller sea lions to adequately nourish their late gestation YOY in the central Aleutian Islands in the early 2000s. Body mass (kg) and percent total body lipid content (% TBL ) increased with age in all three regions of Alaska that were sampled ( P P TBL measured by isotope dilution. The trend for Aleutian Island YOY to have larger body mass and larger body fat reserves are counter to what would be expected if dams were unable to adequately provision their late lactation YOY due to inadequate food availability in the central Aleutian Islands.

Candidatus Desulfofervidus auxilii, a hydrogenotrophic sulfate‐reducing bacterium involved in the thermophilic anaerobic oxidation of methane - Viola Krukenberg; Katie Harding; Michael Richter; Frank Oliver Glöckner; Harald R. Gruber‐Vodicka; Birgit Adam; Jasmine S. Berg; Katrin Knittel; Halina E. Tegetmeyer; Antje Boetius; Gunter Wegener (Environmental Microbiology, 2016)
Summary The anaerobic oxidation of methane (AOM) is mediated by consortia of anaerobic methane‐oxidizing archaea (ANME) and their specific partner bacteria. In thermophilic AOM consortia enriched from Guaymas Basin, members of the ANME‐1 clade are associated with bacteria of the HotSeep‐1 cluster, which likely perform direct electron exchange via nanowires. The partner bacterium was enriched with hydrogen as sole electron donor and sulfate as electron acceptor. Based on phylogenetic, genomic and metabolic characteristics we propose to name this chemolithoautotrophic sulfate reducer Candidatus Desulfofervidus auxilii. Ca . D. auxilii grows on hydrogen at temperatures between 50°C and 70°C with an activity optimum at 60°C and doubling time of 4–6 days. Its genome draft encodes for canonical sulfate reduction, periplasmic and soluble hydrogenases and autotrophic carbon fixation via the reductive tricarboxylic acid cycle. The presence of genes for pili formation and cytochromes, and their similarity to genes of Geobacter spp., indicate a potential for syntrophic growth via direct interspecies electron transfer when the organism grows in consortia with ANME. This first ANME‐free enrichment of an AOM partner bacterium and its characterization opens the perspective for a deeper understanding of syntrophy in anaerobic methane oxidation.

Long-Term Trends of Nutrients and Phytoplankton in Chesapeake Bay - L. W. Harding; C. L. Gallegos; E. S. Perry; W. D. Miller; J. E. Adolf; M. E. Mallonee; H. W. Paerl (Estuaries and Coasts, 2016)

Identifying Catchment-Scale Predictors of Coal Mining Impacts on New Zealand Stream Communities - Joanne E. Clapcott; Eric O. Goodwin; Jon S. Harding (Environmental Management, 2016)

Physicochemical predictors of the invasive diatom Didymosphenia geminata at multiple spatial scales in New Zealand rivers - Jonathan Bray; Jon S. Harding; Cathy Kilroy; Paul Broady; Philippe Gerbeaux (Aquatic Ecology, 2016)

Early Cretaceous palynostratigraphy of the Abu Tunis 1x borehole, northern Western Desert, Egypt, with emphasis on the possible palaeoclimatic effect upon the range of Dicheiropollis etruscus in North Africa - Amr S. Deaf; Ian C. Harding; John E.A. Marshall (Palynology, 2016)

A Geoenvironmental Model for Orogenic Gold Deposits to Predict Potential Environmental Effects - Dave Craw; Jo Cavanagh; Joanna Druzbicka; Jon S. Harding; Gemma Kerr; James Pope; Dave Trumm (Mine Water and the Environment, 2015)

Initial evaluations of a Gulf of Mexico/Caribbean ocean forecast system in the context of the Deepwater Horizon disaster - Edward D. Zaron; Patrick J. Fitzpatrick; Scott L. Cross; John M. Harding; Frank L. Bub; Jerry D. Wiggert; Dong S. Ko; Yee Lau; Katharine Woodard; Christopher N. K. Mooers (Frontiers of Earth Science, 2015)

Stream biomonitoring using macroinvertebrates around the globe: a comparison of large-scale programs - Daniel F. Buss; Daren M. Carlisle; Tae-Soo Chon; Joseph Culp; Jon S. Harding; Hanneke E. Keizer-Vlek; Wayne A. Robinson; Stephanie Strachan; Christa Thirion; Robert M. Hughes (Environmental Monitoring and Assessment, 2015)

“Agro-meteorological indices and climate model uncertainty over the UK” - A. E. Harding; M. Rivington; M. J. Mineter; S. F. B. Tett (Climatic Change, 2015)

Designing a sustainable monitoring framework for assessing impacts of climate change at Joshua Tree National Park, USA - Cameron W. Barrows; Josh Hoines; Kathleen D. Fleming; Michael S. Vamstad; Michelle Murphy-Mariscal; Kristen Lalumiere; Mitzi Harding (Biodiversity and Conservation, 2014)

Variable survival across low pH gradients in freshwater fish species - P. G. Jellyman; J. S. Harding (Journal of Fish Biology, 2014)
A series of 14 day experiments was conducted on five common New Zealand fish species (redfin bully Gobiomorphus huttoni , inanga Galaxias maculatus , brown trout Salmo trutta , longfin eel Anguilla dieffenbachii and koaro Galaxias brevipinnis ) to assess the effect of pH on survival and changes in body mass. No species survived in water of pH pH 4·5, G. maculatus larvae were also tested and had high mortality at this pH . Results suggest that adults are tolerant of low‐ pH waters; however, successful remediation of anthropogenically acidified streams will require an understanding of the susceptibility to low pH on different life cycle stages.

Carrageenan analysis. Part 2: Quantification in swine-adapted infant formula - William R. Blakemore; S. Karina Kwok; Niles I. Harding (Food Additives & Contaminants: Part A, 2014)

Cretaceous (Albian–?early Santonian) palynology and stratigraphy of the Abu Tunis 1x borehole, northern Western Desert, Egypt - Amr S. Deaf; Ian C. Harding; John E. A. Marshall (Palynology, 2014)

Scientific Bases for Numerical Chlorophyll Criteria in Chesapeake Bay - L. W. Harding; R. A. Batiuk; T. R. Fisher; C. L. Gallegos; T. C. Malone; W. D. Miller; M. R. Mulholland; H. W. Paerl; E. S. Perry; P. Tango (Estuaries and Coasts, 2014)

Leaf breakdown, detrital resources, and food webs in streams affected by mine drainage - Kristy L. Hogsden; Jon S. Harding (Hydrobiologia, 2013)

Crop protection and mortality of Agriotes obscurus wireworms with blended insecticidal wheat seed treatments - Robert S. Vernon; Willem G. van Herk; Markus Clodius; Chantelle Harding (Journal of Pest Science, 2013)

Diatom community response to an acid mine drainage gradient - Kate A. Schowe; Jon S. Harding; Paul A. Broady (Hydrobiologia, 2013)

EPG monitoring of the probing behaviour of the common brown leafhopper Orosius orientalis on artificial diet and selected host plants - Piotr Trębicki; W. Fred Tjallingii; Rob M. Harding; Brendan C. Rodoni; Kevin S. Powell (Arthropod-Plant Interactions, 2012)

Trade-off in ecosystem services of the Somerset Levels and Moors wetlands - M. C. Acreman; R. J. Harding; C. Lloyd; N. P. McNamara; J. O. Mountford; D. J. Mould; B. V. Purse; M. S. Heard; C. J. Stratford; S. J. Dury (Hydrological Sciences Journal, 2011)

Adverse foraging conditions may impact body mass and survival of a high Arctic seabird - Ann M. A. Harding; Jorg Welcker; Harald Steen; Keith C. Hamer; Alexander S. Kitaysky; Jérôme Fort; Sandra L. Talbot; Leslie A. Cornick; Nina J. Karnovsky; Geir W. Gabrielsen; David Grémillet (Oecologia, 2011)

Carbon Cycling in Floodplain Ecosystems: Out-Gassing and Photosynthesis Transmit Soil δ13C Gradient Through Stream Food Webs - Duncan P. Gray; Jon S. Harding; Bo Elberling; Travis Horton; Tim J. Clough; Mike J. Winterbourn (Ecosystems, 2011)

Temporal change in UK marine communities: trends or regime shifts? - M. Spencer; S. N. R. Birchenough; N. Mieszkowska; L. A. Robinson; S. D. Simpson; M. T. Burrows; E. Capasso; P. Cleall‐Harding; J. Crummy; C. Duck; D. Eloire; M. Frost; et al. (Marine Ecology, 2011)
A regime shift is a large, sudden, and long‐lasting change in the dynamics of an ecosystem, affecting multiple trophic levels. There are a growing number of papers that report regime shifts in marine ecosystems. However, the evidence for regime shifts is equivocal, because the methods used to detect them are not yet well developed. We have collated over 300 biological time series from seven marine regions around the UK, covering the ecosystem from phytoplankton to marine mammals. Each time series consists of annual measures of abundance for a single group of organisms over several decades. We summarised the data for each region using the first principal component, weighting either each time series or each biological component ( e.g. plankton, fish, benthos) equally. We then searched for regime shifts using Rodionov’s regime shift detection (RSD) method, which found regime shifts in the first principal component for all seven marine regions. However, there are consistent temporal trends in the data for six of the seven regions. Such trends violate the assumptions of RSD. Thus, the regime shifts detected by RSD in six of the seven regions are likely to be artefacts caused by temporal trends. We are therefore developing more appropriate time series models for both single populations and whole communities that will explicitly model temporal trends and should increase our ability to detect true regime shift events.

Multi-scale calculation and global-fit analysis of hydrodynamic properties of biological macromolecules: determination of the overall conformation of antibody IgG molecules - D. Amorós; A. Ortega; S. E. Harding; J. García de la Torre (European Biophysics Journal, 2010)

Structure and heterogeneity of gliadin: a hydrodynamic evaluation - Shirley Ang; Jana Kogulanathan; Gordon A. Morris; M. Samil Kök; Peter R. Shewry; Arthur S. Tatham; Gary G. Adams; Arthur J. Rowe; Stephen E. Harding (European Biophysics Journal, 2010)

Metal contamination in aquatic environments: science and lateral management. By Samuel N.Luoma and Philip S.Rainbow. Published in 2008 by Cambridge University Press, Cambridge, United Kingdom (www.cambridge.org). 573 p, hardcover. ISBN 978–0‐521–86057–4. Price au$200.00. - Jon S. Harding (New Zealand Journal of Marine and Freshwater Research, 2009)

Traditional Fisheries of Antongil Bay, Madagascar - P Doukakis; M Jonahson; V Ramahery; B.J De Dieu Randriamanantsoa; S Harding (Western Indian Ocean Journal of Marine Science, 2009)

Polymorphism at the avpr1a locus in male prairie voles correlated with genetic but not social monogamy in field populations - N. G. SOLOMON; A. R. RICHMOND; P. A. HARDING; A. FRIES; S. JACQUEMIN; R. L. SCHAEFER; K. E. LUCIA; B. KEANE (Molecular Ecology, 2009)
Integrative studies of genetics, neurobiology and behaviour indicate that polymorphism in specific genes contributes to variation observed in some complex social behaviours. The neuropeptide arginine vasopressin plays an important role in the regulation of a variety of social behaviours, including social attachment of males to females, through its action on the vasopressin 1a receptor (V1aR). In socially monogamous prairie voles ( Microtus ochrogaster ), polymorphism in the length of microsatellite DNA within the regulatory region of the gene ( avpr1a ) encoding the V1aR predicts differences among males in neural expression of V1aRs and partner preference under laboratory conditions. However, understanding the extent to which V1aR mediates variation in prairie vole social and reproductive behaviour observed in nature requires investigating the consequences of avpr1a polymorphism and environmental influences under ecologically relevant conditions. We examined the relationship between avpr1a length polymorphism and monogamy among male prairie voles living in 0.1 ha enclosures during a time similar to their natural lifespan. We found no evidence that avpr1a genotype of males predicts variation in social monogamy measured in the field but some indices of social monogamy were affected by population density. Parentage data indicated that a male’s avpr1a genotype significantly influenced the number of females with which he sired offspring and the total number of offspring sired. Total brain concentrations of V1aR mRNA were not associated with either male behaviour or avpr1a genotype. These data show that melding ecological field studies with neurogenetics can substantially augment our understanding of the effects of genes and environment on social behaviours.

Infectious exposure in the first year of life and risk of central nervous system tumors in children: analysis of day care, social contact, and overcrowding - N. J. Harding; J. M. Birch; S. J. Hepworth; P. A. McKinney (Cancer Causes & Control, 2009)

Design and application of two novel degenerate primer pairs for the detection and complete genomic characterization of potyviruses - C. Ha; S. Coombs; P. A. Revill; R. M. Harding; M. Vu; J. L. Dale (Archives of Virology, 2008)

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

Persistence of a significant population of rare Canterbury mudfish ( Neochanna burrowsius ) in a hydrologically isolated catchment - Jon S. Harding; David A. Norton; Angus R. McIntosh (New Zealand Journal of Marine and Freshwater Research, 2007)
Canterbury mudfish ( Neochanna burrowsius ) are endemic to a small region of Canterbury, South Island, New Zealand and classified as nationally endangered. We reviewed data from the New Zealand Freshwater Fish Database and trapped fish in July 2006, and January and February 2007 in the Waianiwaniwa Valley, Canterbury to determine the importance of this catchment for mudfish conservation. Mudfish were found in 19 of the 28 sites sampled. Waianiwaniwa Valley sites accounted for 47% of all Canterbury mudfish database records of mean catch per unit effort (CPUE) ≥6 fish. The population comprised young recruits ( 120mm TL) indicating a healthy population. Drying of the lower mainstem, and low dissolved oxygen levels in summer create a unique catchment free of larger predatory fish and with reduced competition from other fish species. We estimated that mudfish occur in at least 24.3 km of the Waianiwaniwa River, making this catchment the most important refuge known for the conservation of this species.

Evaluation of potato production best management practices - Bryan G. Hopkins; Donald A. Horneck; Mark J. Pavek; Brad D. Geary; Nora L. Olsen; Jason W. Ellsworth; George D. Newberry; Jeff S. Miller; Robert E. Thornton; Gale W. Harding (American Journal of Potato Research, 2007)

Spatial biodiversity patterns in a large New Zealand braided river - Duncan Gray; Mike R. Scarsbrook; Jon S. Harding (New Zealand Journal of Marine and Freshwater Research, 2006)
At the catchment scale, braided rivers are recognised as physically unstable, dynamic landscapes, yet at finer spatial scales they are a mosaic of micro‐habitats including physically unstable braided channels and more stable spring‐sources, spring creeks, and groundwater zones. We investigated benthic invertebrate communities at 103 sites in braided channels, springs and hillslope streams in the Waimakariri River, New Zealand over 3 months. One hundred taxa were identified, including a number of rare phreatic species. Highest total taxonomic richness occurred in springs (81 taxa), whereas main braids and hillslope streams had fewer taxa (54 and 56, respectively). Spring‐fed habitats also had the highest diversity of unique taxa (22), whereas main channels had five and hillslope streams 11 taxa, respectively. Several taxa including the mayfly Deleatidium and orthoclad chironomids were ubiquitous, whereas others such as the flatworm Prorhynchus had restricted habitats. Our results highlight the high spatial heterogeneity of braided river habitats and the importance of springs as centres of invertebrate diversity within braided river catchments.

Can forest fragments reset physical and water quality conditions in agricultural catchments and act as refugia for forest stream invertebrates? - Jon S. Harding; Koen Claassen; Niels Evers (Hydrobiologia, 2006)

Effects of unconditioned and conditioned social defeat on alcohol self-administration and reinstatement of alcohol seeking in rats - D. Funk; S. Harding; W. Juzytsch; A. D. Lê (Psychopharmacology, 2005)

Urocortin 1 expression in five pairs of rat lines selectively bred for differences in alcohol drinking - V. F. Turek; N. O. Tsivkovskaia; P. Hyytia; S. Harding; A. D. Lê; A. E. Ryabinin (Psychopharmacology, 2005)

Role of alpha-2 adrenoceptors in stress-induced reinstatement of alcohol seeking and alcohol self-administration in rats - A. D. L; S. Harding; W. Juzytsch; D. Funk; Y. Shaham (Psychopharmacology, 2005)

Longitudinal patterns in benthic communities in an urban stream under restoration - Tanya J. Blakely; Jon S. Harding (New Zealand Journal of Marine and Freshwater Research, 2005)
Okeover Stream, on the University of Canterbury campus in Christchurch, New Zealand, has been the subject of restoration efforts since 1998. Our study focused on quantifying the response of this urban stream to current restoration efforts. Initially, physico‐chemical conditions and biological communities at three sites along the Okeover Stream were compared with three physically similar sites on each of nearby Waimairi Stream and Avon River. General physical and chemical parameters were similar in all streams with circum‐neutral pH, specific conductivity ranging from 167 to 173 μS/cm, dissolved oxygen ranging from 9.0 to 9.2 mg/litre, low turbidity, and similar hydrological conditions. However, analysis of heavy metals in the sediment showed mean lead (Pb) concentrations in Okeover and Waimairi Streams exceeded ANZECC ISQG‐low trigger values (86.9 and 83.7 mg/kg, respectively), whereas Avon River sediment Pb levels (27.3 mg/ kg) were below trigger values. Benthic taxonomic richness did not differ significantly among the three streams. However, Okeover Stream community was dominated by the amphipod Paracalliopefluviatilis, whereas in Waimairi Stream and Avon River the gastropod snails Potamopyrgus antipodarum and Physella acuta were the dominant benthic fauna. A further assessment made at six sites along 1200 m of Okeover Stream showed no distinct longitudinal patterns in physical or chemical conditions, but there was a strong pattern in benthic macroinvertebrate communities. Taxonomic richness and caddisfly diversity increased downstream, with twice as many taxa at the most downstream site than the uppermost sampling site. In upper reaches, copper (Cu), Pb, and zinc (Zn) concentrations in sediments all exceeded ANZECC ISQG‐low trigger values. Despite ongoing restoration efforts in Okeover Stream, sedimentation, the presence of high heavy metal concentrations, intermittent flows in headwaters, and possible barriers to adult recolonisation seem to be having a continuing negative impact on benthic communities, especially in the headwaters.

Larval lobster ( Homarus americanus ) distribution and drift in the vicinity of the Gulf of Maine offshore banks and their probable origins - G. C. HARDING; K. F. DRINKWATER; C. G. HANNAH; J. D. PRINGLE; J. PRENA; J. W. LODER; S. PEARRE; W. P. VASS (Fisheries Oceanography, 2005)
Surveys for lobster larvae in offshore waters of the north‐eastern Gulf of Maine in 1983, 1987 and 1989 confirm that local hatching occurs mainly at depths

Sugarcane bacilliform virus encapsidates genome concatamers and does not appear to integrate into the Saccharum officinarum genome - R. J. Geijskes; K. S. Braithwaite; G. R. Smith; J. L. Dale; R. M. Harding (Archives of Virology, 2004)

Nicotine increases alcohol self-administration and reinstates alcohol seeking in rats - A. D. Lê; A. Wang; S. Harding; W. Juzytsch; Y. Shaham (Psychopharmacology, 2003)

Historic deforestation and the fate of endemic invertebrate species in streams - Jon S. Harding (New Zealand Journal of Marine and Freshwater Research, 2003)
Deforestation is a global phenomenon threatening the biodiversity of many unique forested ecosystems. The volcanic calderas of Banks Peninsula, New Zealand, experienced widespread deforestation from 1860 to 1900 when >98% of the indigenous forest was removed. Streams on the Peninsula possess several regionally‐endemic species. The objective of this study was to assess the effect of historic deforestation on stream faunas by surveying the distribution of endemic and other benthic invertebrate species in relation to remnant and regenerating indigenous forest fragments. Twenty‐seven sites, in nine catchments were surveyed. Three catchments were dominated by forest, three by farmland, and three were predominantly farmland with forested headwaters. Taxonomic richness was significantly greater in forested streams than agricultural streams, particularly for Ephemeroptera, Plecoptera, and Trichoptera taxa. Distributions of the regionally‐endemic hydrobiosid caddisflies Costachorema peninsulae and Edpercivalia banksiensis were restricted to forest fragments. Two other endemics, the stonefly Zelandobius wardi and the caddisfly Hydrobiosis styx , were rarely collected but seemed to be restricted to headwater sites in forest. In contrast, the blepharicerid Neocurupira chiltoni was widely distributed in streams, regardless of land cover, and in relative abundances unrelated to site location within the catchment. Evidence from Banks Peninsula streams suggests that throughout New Zealand a number of species unknown to science may have been lost because of past deforestation, and that remnant forested habitats may be vital to the conservation and preservation of regionally endemic species.

Sequence analysis of an Australian isolate of sugarcane bacilliform badnavirus - R. J. Geijskes; K. S. Braithwaite; J. L. Dale; R. M. Harding; G. R. Smith (Archives of Virology, 2002)

Lidar remote sensing of above‐ground biomass in three biomes - Michael A. Lefsky; Warren B. Cohen; David J. Harding; Geoffrey G. Parker; Steven A. Acker; S. Thomas Gower (Global Ecology and Biogeography, 2002)
Estimation of the amount of carbon stored in forests is a key challenge for understanding the global carbon cycle, one which remote sensing is expected to help address. However, estimation of carbon storage in moderate to high biomass forests is difficult for conventional optical and radar sensors. Lidar ( li ght d etection and r anging) instruments measure the vertical structure of forests and thus hold great promise for remotely sensing the quantity and spatial organization of forest biomass. In this study, we compare the relationships between lidar‐measured canopy structure and coincident field measurements of above‐ground biomass at sites in the temperate deciduous, temperate coniferous, and boreal coniferous biomes. A single regression for all three sites is compared with equations derived for each site individually. The single equation explains 84% of variance in above‐ground biomass ( P

Promoters derived from banana bunchy top virus-associated components S1 and S2 drive transgene expression in both tobacco and banana - S. Hermann; D. Becker; R. Harding; J. Dale (Plant Cell Reports, 2001)

Progress in understanding of land surface/atmosphere exchanges at high latitudes - R. J. Harding; S.-E. Gryning; S. Halldin; C. R. Lloyd (Theoretical and Applied Climatology, 2001)

Analysis of chromatin, nuclear DNA and organelle composition in somatic hybrids between Solanum tuberosum and Solanum sanctae-rosae - K. Harding; S. Millam (Theoretical and Applied Genetics, 2000)

The role of corticotrophin-releasing factor in stress-induced relapse to alcohol-seeking behavior in rats - A. D. Lê; S. Harding; W. Juzytsch; J. Watchus; U. Shalev; Y. Shaham (Psychopharmacology, 2000)

5′-Anchored simple-sequence repeat primers are useful for analysing potato somatic hybrids - D. Matthews; J. McNicoll; K. Harding; S. Millam (Plant Cell Reports, 1999)

The reduction in alcohol intake in rats by isoproterenol is attenuated by indomethacin but not enalapril: relationship to blood glucose levels - L. A. Grupp; V. Lau; S. Harding (Psychopharmacology, 1998)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Pituitary and plasma AVT content in the flounder (Platichthys flesus) - K.E. Harding; J.M. Warne; S. Hyodo; R.J. Balment (Fish Physiology and Biochemistry, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Mapping of the gene encoding the B56β subunit of protein phosphatase 2A (PPP2R5B) to a 0.5-Mb region of chromosome 11q13 and its exclusion as a candidate gene for multiple endocrine neoplasia type 1 (MEN1) - S. A. Forbes; A. A. J. Pannett; J. H. D. Bassett; B. Harding; C. Wooding; R. V. Thakker; R. Butler; D. Ogilvie; R. Anand; P. Gaudray; G. Weber; C. Larsson; et al. (Human Genetics, 1997)

Strategies for coexistence in two species of New Zealand Hydropsychidae (Trichoptera) - Jon S. Harding (Hydrobiologia, 1997)

A polydisperse linear random coil model for the quaternary structure of pig colonic mucin - Kornelia Jumel; Fiona J. J. Fogg; David A. Hutton; J. P. Pearson; Adrian Allen; S. E. Harding (European Biophysics Journal, 1997)

Characterisation of the low affinity interaction between rat cell adhesion molecules CD2 and CD48 by analytical ultracentrifugation - H. Silkowski; S. J. Davis; A. Neil Barclay; Arthur J. Rowe; Stephen E. Harding; Olwyn Byron (European Biophysics Journal, 1997)

Low temperature solution behaviour of Methylophilus methylotrophus electron transferring flavoprotein: a study by analytical ultracentrifugation - H. Cölfen; S. E. Harding; Emma K. Wilson; Nigel S. Scrutton; Donald J. Winzor (European Biophysics Journal, 1997)

A trimeric, alpha-helical, coiled coil peptide: association stoichiometry and interaction strength by analytical ultracentrifugation - R. M. Thomas; A. Zampieri; K. Jumel; S. E. Harding (European Biophysics Journal, 1997)

The ELLIPS suite of macromolecular conformation algorithms - S. E. Harding; John C. Horton; H. Cölfen (European Biophysics Journal, 1997)

A slot-blot hybridisation method for screening somatic hybrids - D. Matthews; K. Harding; M. J. Wilkinson; S. Millam (Plant Molecular Biology Reporter, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

A gene tree for β-globin sequences from melanesia - R. M. Harding; S. M. Fullerton; R. C. Griffiths; J. B. Clegg (Journal of Molecular Evolution, 1997)

Detection and characterization of pangola stunt Fijivirus from Australia using cloned cDNA probes - M. Karan; J. L. Dale; M. F. Bateson; R. M. Harding; D. S. Teakle (Archives of Virology, 1994)